FRI0088 SAFETY, IMMUNOGENICITY AND EFFICACY OF THE PROPOSED BIOSIMILAR MSB11022 (MODIFIED FORMULATION) COMPARED WITH ADALIMUMAB REFERENCE PRODUCT IN PATIENTS WITH MODERATELY TO SEVERELY ACTIVE RHEUMATOID ARTHRITIS: AURIEL-RA, A RANDOMISED, DOUBLE-BLIND, PHASE III STUDY. (June 2019) - Edwards, Christopher; Chyrok, Veronica; Monnet, Joëlle; Ullmann, Martin; Vlachos, Pantelis
Abstract : Background: Adalimumab is a fully human anti-TNF monoclonal antibody indicated for the treatment of multiple inflammatory disorders, including rheumatoid arthritis (RA). MSB11022 is a proposed adalimumab biosimilar that has been shown to be structurally and functionally similar to the adalimumab reference product 1 . MSB11022 has been developed in two formulations, in a citrate-based buffer, and in a modified buffer and stabiliser. MSB11022 demonstrated bioequivalence and comparable safety, tolerability and immunogenicity profiles to reference adalimumab (both in citrate formulations) in a study in healthy volunteers 2 . Subsequently MSB11022 was shown to be therapeutically equivalent to reference adalimumab (both citrate formulations) in terms of efficacy, safety and immunogenicity in psoriasis patients in the 52-week, Phase III, pivotal AURIEL-PsO study 3 . MSB11022 (modified formulation) demonstrated bioequivalence and a comparable safety and immunogenicity profile to MSB11022 (citrate formulation) in an additional healthy volunteer study (EMR200588-003) 4 . Objectives: To evaluate safety, immunogenicity and efficacy of MSB11022 (modified formulation) in patients with moderately to severe active rheumatoid arthritis compared to reference adalimumab up to 52 weeks. Methods: RA patients receiving methotrexate were randomised 1:1 to MSB11022 (modified formulation) or reference adalimumab (citrate formulation) in the double-blind, multicentre, phase III AURIEL-RA study (NCT03052322 ). Safety, efficacy and immunogenicity endpoints were assessed at scheduled visits up to week 52 using descriptive statistical methods only. Safety was the primary objective and the study was not powered to demonstrate equivalent efficacy. Results: 288 RA patients were randomised (MSB11022, n = 143; reference adalimumab, n = 145). Patient baseline characteristics were comparable between treatment groups. Few adverse events of special interest (AESIs) of hypersensitivity (primary endpoint) were reported during the study and the proportions were similar across treatment arms. Efficacy endpoints, including the key secondary endpoint of American College of Rheumatology criteria 20% (ACR20) response rate at week 12, were similar between the treatment arms. The safety profiles of patients receiving MSB11022 and reference adalimumab were also similar through to week 52. There were no clinically meaningful differences in the incidence of anti-drug antibodies (ADAs) and neutralising antibodies (NAbs) between treatment arms up to week 52. Key results are presented in Table 1 . Conclusion: MSB11022 (modified formulation) and reference adalimumab had similar safety, immunogenicity and efficacy profiles over 52 weeks in patients with RA, supplementing the clinical data collected with MSB11022 (citrate formulation) in healthy volunteers and psoriasis patients References: [1] Magnenat L, et al. MAbs 2017;9(1):127-39. [2] Hyland E, et al. Br J Clin Pharmacol 2016;82(4):983-93. [3] Hercogova J, et al. J Am Acad Dermatol 2018;79(3):AB21. [4] Fresenius Kabi. Data on File 2019 Disclosure of Interests: Christopher Edwards Grant/research support from: Abbvie, BMS, Biogen, Celgene, Fresenius, Janssen, Lilly, Mundipharma, Pfizer, MSD, Novartis, Roche, Samsung, Sanofi, UCB, Consultant for: Abbvie, BMS, Biogen, Celgene, Fresenius, Janssen, Lilly, Mundipharma, Pfizer, MSD, Novartis, Roche, Samsung, Sanofi, UCB, Speakers bureau: Abbvie, BMS, Biogen, Celgene, Fresenius, Janssen, Lilly, Mundipharma, Pfizer, MSD, Novartis, Roche, Samsung, Sanofi, UCB, Veronica Chyrok Employee of: Former employee of Fresenius Kabi SwissBioSim, Joëlle Monnet Employee of: Employee of Fresenius Kabi SwissBioSim, Martin Ullmann Shareholder of: Amgen, BMS, Employee of: Employee of Fresenius Kabi SwissBioSim, Pantelis Vlachos: None declared